2016
DOI: 10.1089/bfm.2016.0022
|View full text |Cite
|
Sign up to set email alerts
|

Do American Colleges and Universities Support the Lactation Needs of Students?

Abstract: The vast majority of the sample did not have a policy for lactating students, and almost half of the schools did not have designated space for milk expression accessible to students. Lactating students will likely encounter challenges in simultaneously sustaining breastfeeding and meeting their educational goals in these contexts. To meet the recommendation of the American Academy of Pediatrics of 6 months of exclusive breastfeeding and continued breastfeeding for 1 year or more, American colleges and universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 7 publications
2
22
0
1
Order By: Relevance
“…In contrast, few studies have considered the experiences of breastfeeding people returning to school. A consistent finding among these studies is that breastfeeding students often lack a private space to express their milk on campus (Bostick et al, 2016;Dinour & Beharie, 2015).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…In contrast, few studies have considered the experiences of breastfeeding people returning to school. A consistent finding among these studies is that breastfeeding students often lack a private space to express their milk on campus (Bostick et al, 2016;Dinour & Beharie, 2015).…”
Section: Introductionmentioning
confidence: 57%
“…Lactation space improvement could influence student-parent experience across the US. According to an assessment of higher-education lactation policies by Bostick and colleagues, 55% of colleges and universities have designated lactation spaces accessible to their students (Bostick et al, 2016). The experiences and preferences identified by students at the UW may be applicable to student-parents in other university settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of suitable breastfeeding spaces clearly affects individual behaviour. A survey of higher education institutions in the United States revealed that the lowest number of breastfeeding rooms was 0.02 per 1000 students and the highest was 1.49 per 1000 students [42]. Some university campuses had a policy that placed the responsibility on the academic staff member to find a suitable space for students who are breastfeeding or expressing, when designated spaces were located too far away.…”
Section: Discussionmentioning
confidence: 99%
“…Some university campuses had a policy that placed the responsibility on the academic staff member to find a suitable space for students who are breastfeeding or expressing, when designated spaces were located too far away. Yet other campuses had ample spaces, access to lactation consultants and even provided breast pumps for student use [42]. Availability of these resources conveys to students that the university supports breastfeeding mothers and it transforms the environment into an enabling one.…”
Section: Discussionmentioning
confidence: 99%